Local Revenue and Financial Independence on Economic Growth Through Capital Expenditure - Made Setini, N. P. Y. Ria Sawitri, L. P. V. I. Perdanawati, N. N. Sudiyani, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
This study aims to analyze changes in regional income and financial independence of regional economic growth with capital expenditure as a variable intervention in Denpasar City in 2017-2019. This exploration technique is a graphic subjective strategy with the cooperation of region and regional government in Denpasar 2017-2019. This study used the purposive sampling method. Test results show that the Regional Revenue directly has a positive effect on regional economic growth while financial independence does not directly affect regional economic growth, and capital expenditure cannot mediate local income growth and financial independence on economic growth.